Coping with Reading Difficulty Using Socio-Affective Strategy - Rahman, Sharifah Amani Syed Abdul; Yunos, D Rohayu Mohd; Rahmat, Noor Hanim; Rahim, Puteri Rohani Megat Abdul; Anuarudin, Aini Andria Shirin (International Journal of Asian Social Science, 2021)
Reading academic texts requires learners to use a variety of skills and strategies. Among the main types of academic reading are (a) reading for quick reference, (b) reading for pleasure and also (c) critical reading. Students who have just left high schools, reading academic text may post some problems. Hence, readers face challenges when they read academic texts. Different readers face different difficulties when they read different types of texts. Some readers face linguistics challenges while some face non-linguistic challenges when they read academic texts. Fortunately, many academic readers have their own way to cope with the difficulties in reading. This study explored the problem readers face when they read academic texts. This study also investigates show readers use schemata and socio affective strategies to help them cope with difficulties when reading academic texts. The instrument used is a five Likert scale survey with 33 items. Data is analyzed using SPSS version 26 to reveal frequency of responses. Findings bear interesting pedagogical implications to the teaching and learning of academic reading.